Redetermination of 3-(ammoniomethyl)pyridinium dichloride - Liang, Wen-Xian (International Union of Crystallography, 2009)
The crystal structure of the title compound, C(6)H(10)N(2) (2+)·2Cl(−), has been reported previously in the non-standard setting P2(1)/a [Genet (1965 ▶). Bull. Soc. Fr. Miner. Crist. 88, 463–470], with an R value of 0.16. The current redetermination improves significantly the precision of the geometric parameters. In the crystal packing, cations and anions are linked by intermolecular N—H⋯Cl and C—H⋯Cl hydrogen bonds into a three-dimensional network.